Embryonic heart rate predicts prenatal development rate, but is not related to post‐natal growth rate or activity level in the zebra finch (Taeniopygia guttata). (17th October 2018) - Sheldon, Elizabeth L.; Griffith, Simon C.
Abstract: Inter‐individual variation in behaviour has been the focus of much recent work, yet the underlying mechanisms that cause and maintain this variation are unclear. It has been proposed that consistent individual differences in metabolism could be related to inter‐individual variation in behaviour and development throughout life. Here, we tested this idea in the zebra finch ( Taeniopygia guttata ), by investigating whether embryonic heart rate (a proxy for metabolic rate) is associated with prenatal developmental rates, post‐natal activity levels and post‐natal growth rates. Embryonic heart rate and post‐natal activity level were significantly repeatable throughout an individual's development, such that consistent individual differences in these traits could be distinguished. We detected a significant, negative relationship between embryonic heart rate and incubation duration. However, we did not detect any relationship between embryonic heart rate, post‐natal activity levels or post‐natal growth rates. Our findings are significant because they identify consistent individual differences in embryonic metabolic phenotype and post‐natal traits. However, we were unable to identify any correlation between the pre‐ and post‐natal phenotypes suggesting that either intrinsic metabolic differences do not persist across the developmental boundary of hatching or such differences become obscured by parental or environmental effects after hatching. Our findings raise a number of questions about possible selection on metabolic phenotypes, both before and after hatching, and why developmental trajectories before and after hatching are apparently unlinked.